'Scott of the Antarctic' on the German Stage: Reinhard Goering's Die Südpolexpedition des Kapitäns Scott - Hanne Nielsen; Elizabeth Leane (2013)
Reinhard Goering’s play Die Südpolexpedition des Kapitäns Scott (1929) tells the story of the famously tragic British polar expedition led by Robert F. Scott in 1911-1912. As the first public staging of the story, the play created considerable controversy in Britain when it premiered in Berlin in 1930. A late Expressionist drama, it offered perspectives on the expedition quite different to those coming out of Scott’s homeland. In this article, Hanne Nielsen and Elizabeth Leane contextualize the play within Goering’s own career; outline its performance history; examine its reception in both Germany and Britain; and analyze the play text in terms of its innovative treatment of Scott’s story.